Analisis Sistem Antrian Pada Umkm Kedai Beansnomo Coffe Dalam Upaya Peningkatan Efesiensi Pelayanan - Marianti, Nike; Erviyanti, Anggi; Pratiwi, Cindi; Dasopang, Khoirunisa; Ritonga, Irmayanti (Journal of Computer Science and Information System(JCoInS), 2024)
The aim of the research is to analyze the Queuing System at the UMKM  BEANSNOMO COFFE Shop in an effort to increase service efficiency. This research method conducted direct interviews with the owner and used non-probability sample determination. The research results obtained were that the Beansnomo Coffee Shop uses an unlimited population arrival system, with queuing discipline referring to the First-In, First-Out discipline rules. (FIFO) is the most common queue where customers who arrive first (arrive) are served first (leave). With professional treatment, service efficiency can be increased. Based on the results of the respondent table, it can be seen that men are more interested in coffee lovers than women, both young and old. This research can still be developed, so it is recommended for future researchers to use other methods for comparison.